Pengaruh Kualitas Pelayanan, Harga Dan Lokasi Terhadap Keputusan Pembelian Konsumen Pada Rumah Makan - Suharlina, Suharlina (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
The aim of this study is to determine the effect of service quality, price and location on purchasing decisions at Berkah Restaurant, Sampaga District, Mamuju Regency and to determine the effect of service quality, price and location simultaneously on purchasing decisions at Berkah Restaurant, Sampaga District. Mamuju Regency. The types used are quantitative and qualitative data and the data sources are primary and secondary data. The results of the calculation of the Cochran formula show that the number of samples in this study were 96 respondents. Data analysis methods namely Validity Test, Reliability Test, Multiple Linear Regression. Based on the results of the analysis tests carried out, the results obtained show that service quality, price, and location have a partially significant effect on purchasing decisions at the Berkah Restaurant, Sampaga District, Mamuju Regency and for service quality, price, and location have a simultaneous and significant effect on decisions purchase at the Berkah Restaurant, Sampaga District, Mamuju Regency.